Optimization of coplanar high rate supercapacitors - Sun, Leimeng (2018)
In this work, we describe two efficient methods to enhance the electrochemical performance of high-rate coplanar micro-supercapacitors (MSCs). Through introducing MnO2 nanosheets on vertical-aligned carbon nanotube (VACNT) array, the areal capacitance and volumetric energy density exhibit tremendous improvements which have been increased from 0.011 mF cm−2 to 0.017 mWh cm−3 to 0.479 mF cm−2 and 0.426 mWh cm−3 respectively at an ultrahigh scan rate of 50000 mV s−1. Subsequently, by fabricating an asymmetric MSC, the energy density could be increased to 0.167 mWh cm−3 as well. Moreover, as a result of applying MnO2/VACNT as the positive electrode and VACNT as the negative electrode, the cell operating voltage in aqueous electrolyte could be increased to as high as 2.0 V. Our advanced planar MSCs could operate well at different high scan rates and offer a promising integration potential with other in-plane devices on the same substrate.